Lymphangiogenesis and Lymphangiogenic Growth Factors - Hartiala, Pauliina; Saarikko, Anne M. (Journal of Reconstructive Microsurgery, 2016)
Lymphedema is a progressive disease caused by damage to the lymphatic network. Recent development in the fields of preclinical growth factor research and lymphedema microsurgery promise new hope for lymphedema patients. In this article, we review the latest results on basic research and highlight the role of specific growth factors in normal lymphatic development and several disease states. Lymph node transfer, a new promising method in reconstructive lymphatic microsurgery, is also dependent on the lymphatic vascular regrowth and lymphangiogenic growth factors. We discuss the scientific basis of lymph node transfer and therapeutic potential of lymphangiogenic growth factors in the treatment of lymphedema.
Keywords: lymphangiogenesis; lymph node transfer; VEGF-C